2008
DOI: 10.3354/meps07755
|View full text |Cite
|
Sign up to set email alerts
|

Inter-oceanic analysis of demographic variation in a widely distributed Indo-Pacific coral reef fish

Abstract: The surgeonfish Ctenochaetus striatus is abundant and widely distributed on reefs throughout the Indian and Pacific Oceans. Population samples at 15 sites that spanned 158°of longitude and 40°of latitude across both hemispheres of the Indian and Pacific oceans allowed us to examine geographic variation in longevity, growth rate and adult size of this species. Samples from 5 sites in the Indian Ocean, 6 in the western Pacific and 4 in the central Pacific provided otolith-based estimates of size-at-age for 1537 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 49 publications
5
89
0
Order By: Relevance
“…We also used the reparameterized version of the VBGF (rVBGF) (Francis 1988a, Moulton et al 1992, Welsford & Lyle 2005, Trip et al 2008:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also used the reparameterized version of the VBGF (rVBGF) (Francis 1988a, Moulton et al 1992, Welsford & Lyle 2005, Trip et al 2008:…”
Section: Methodsmentioning
confidence: 99%
“…The macroandric sister species of yellow tang, Zebrasoma scopas, had a similar T max 25% of 29 to 34 yr among different locations on the Great Barrier Reef, but sexual differences in longevity were not investigated (Choat & Robertson 2002, Trip et al 2008). While survival rates of juveniles in the deeper coral-rich habitat appear to be independent of size ), the presence of size-and sex-dependent survival rates of yellow tang adults, either of which could lead to the slightly higher male longevity, has not been empirically tested.…”
Section: Sexual Differences In Age Size and Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial number of studies have demonstrated latitudinal and temperature effects on patterns of life-history variation [35][36][37]. On smaller spatial scales, sexual demography and the timing of sex change have been shown to vary in coral reef fishes across different reef configurations and reef sizes [4,6,18].…”
Section: Discussionmentioning
confidence: 99%
“…Spatial variation in biological characteristics is a common feature of tropical shallow-water reef fish (Gust et al, 2002;Williams et al, 2003;Carter et al, 2014a,b), including species of lutjanids (Newman et al, 1996a;Kritzer, 2002;Cappo et al, 2013), and has been observed at multiple scales ranging from patch reefs on the same reef system (<1 km) (Pitcher, 1992;Gust et al, 2002) to thousands of kilometers across an ocean basin (Choat et al, 2003;Robertson et al, 2005) as well as between oceans (Trip et al, 2008). Many shallow-water species display a metapopulation structure (Kritzer and Sale, 2006), with spatial separation of adult sub-populations linked to varying degrees by a pelagic larval stage.…”
Section: Introductionmentioning
confidence: 99%